2002
DOI: 10.1046/j.1468-3083.2002.00543.x
|View full text |Cite
|
Sign up to set email alerts
|

Sebaceus naevi: a clinicopathologic study

Abstract: The incidence of malignancy arising on SN was very low, indicating that prophylactic surgery of NS in children is not recommendable. Developmental defects should be investigated in order to evidence possible epidermal naevus syndrome associated with SN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
49
1
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 33 publications
(48 reference statements)
4
49
1
3
Order By: Relevance
“…Nevus sebaceus (NS) is a congenital hamartoma that combines a variety of epidermal, hair follicle, sebaceous, and apocrine gland abnormalities. NS is detected in 0.5–1% of all dermatologic patients . It often presents at birth but may not become apparent until later in life.…”
Section: Introductionmentioning
confidence: 99%
“…Nevus sebaceus (NS) is a congenital hamartoma that combines a variety of epidermal, hair follicle, sebaceous, and apocrine gland abnormalities. NS is detected in 0.5–1% of all dermatologic patients . It often presents at birth but may not become apparent until later in life.…”
Section: Introductionmentioning
confidence: 99%
“…Nevus sebaceus (NS), first described by Jadassohn, is a complex hamartoma usually found on the face or scalp and exhibits alopecia with epidermal hyperplasia, malformed hair follicle, sebaceous and ectopic apocrine glands to varying degrees microscopically. It may evolve through three stages clinically, including alopecia stage, verrucous or papillomatous plaque stage, and tumor stage 1 . In 2008, Correale et al.…”
mentioning
confidence: 99%
“…2 Studies of large numbers of NS found syringocystadenoma papilliferum and trichoblastoma/basal cell carcinoma to be the most common. [3][4][5] Less frequent neoplasms reported include leiomyoma, 6 spiradenoma, 7 eccrine syringofibroadenoma, 8 follicular hybrid cysts, 9 squamous cell carcinoma, 10 sebaceous carcinoma, 11,12 tricholemmal carcinoma, 13 syringocystadenocarcinoma papilliferum, 14 eccrine porocarcinoma, 15 ductal sweat gland carcinoma, 16 and apocrine carcinoma. 10,17,18 We report a case of an adenocarcinoma with subsequent metastasis arising in association with a NS with multiple neoplastic proliferations.…”
mentioning
confidence: 99%